Comparative evaluation of antibacterial efficacy of conventional glass-ionomer cement and bulk-fill alkasite material when combined with doxycycline and double antibiotic paste containing ciprofloxacin and metronidazole against Streptococcus mutans and Lactobacillus spp.: An in vitro study - Riddhi Shripad Joshi; Niraj S Gokhale; Shivayogi M Hugar; Sanjana P Soneta; Chandrashekhar M Badakar; Vidyavathi H Patil (Wolters Kluwer Medknow Publications, 2020)
Introduction: Glass-ionomer cement (GIC) have been indispensable to pediatric dentistry. Along with these, newer materials like bulk-fill alkasite cement (Cention N) are popularizing. In spite of this, the search is still on for the "ideal" bioactive material which could provide a therapeutic edge. In light of this, incorporation of antibiotics in GIC or newer materials like bulk-fill alkasite cement (Cention N) would provide a novel alternative material to the dentists. Aim: The study was aimed at comparing the antibacterial efficacy of conventional glass-ionomer cement (CGIC) and bulk-fill alkasite cement (Cention N) with doxycycline (DOX) and double antibiotic paste (DAP) containing metronidazole and ciprofloxacin (1.5% w/w) on Streptococcus mutans and Lactobacillus. Materials and Methods: Agar well diffusion method was followed, in which material discs of 10 mm were made and inserted into the wells. Inhibition zones were calculated after incubation for 24 h at 37°C with zone interpretation scale. Results: A highly significant statistical correlation was found between antibacterial efficacy of the control groups (CGIC and bulk-fill alkasite cement [Cention N]) without antibiotics as compared to the experimental group (CGIC and bulk-fill alkasite cement [Cention N] with DOX and DAP), P = 0.0001 and P = 0.0006 for the CGIC group and P = 0.0147 and P = 0.0080 for the Cention N group (P < 0.05). Conclusion: Incorporation of antibiotics significantly enhanced the antibacterial efficacy of CGIC and bulk-fill alkasite cement (Cention N).